2009
DOI: 10.3844/ajassp.2009.1902.1908
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Buoyancy Force in Computational Fluid Dynamics Simulation of a Two-Dimensional Continuous Ohmic Heating Process

Abstract: Problem statement: Earlier work on ohmic heating technique focused on viscous food and foods containing solid particles. In this study, the use of ohmic heating on sterilization of guava juice is carried out. Computational fluid dynamics is used to model and simulate the system. Approach: Investigate the buoyancy effect on the CFD simulation of continuous ohmic heating systems of fluid foods. A two-dimensional model describing the flow, temperature and electric field distribution of non-Newtonian power law gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In orange juice treated with ohmic heating around 96% of the pectin methylesterase activity was reduced as observed by Demirdöven et al [103]. In fruit juices, the use of ohmic heating to inactivate enzymes does not affect the juice flavor [106]. Hashemi et al [107] compared different ohmic heating treatments (150,200, and 250 V; 120 s; 99.4 • C) with the conventional heating process (90 • C; 15 min) for the inactivation of microorganisms in blended citrus juice (sweet lemon and orange).…”
Section: Juice Composition Vs Processing Technologiesmentioning
confidence: 69%
“…In orange juice treated with ohmic heating around 96% of the pectin methylesterase activity was reduced as observed by Demirdöven et al [103]. In fruit juices, the use of ohmic heating to inactivate enzymes does not affect the juice flavor [106]. Hashemi et al [107] compared different ohmic heating treatments (150,200, and 250 V; 120 s; 99.4 • C) with the conventional heating process (90 • C; 15 min) for the inactivation of microorganisms in blended citrus juice (sweet lemon and orange).…”
Section: Juice Composition Vs Processing Technologiesmentioning
confidence: 69%
“…The comericial computational fluid dynamics software (Fluent) was adopted by Salih et al (2009) to study effect of buoyancy force for two dimensional flows. The results showed that the CFD software can predicted the reliable results of momentum and energy.…”
Section: Introductionmentioning
confidence: 99%